2013
DOI: 10.1186/1472-6882-13-185
|View full text |Cite
|
Sign up to set email alerts
|

Bufalin, a component in Chansu, inhibits proliferation and invasion of hepatocellular carcinoma cells

Abstract: BackgroundHepatocellular carcinoma (HCC) is a common and aggressive cancer, and the treatment options are limited for patients with advanced HCC. Bufalin, the major digoxin-like component of the traditional Chinese medicine Chansu, exhibits significant anti-tumor activities in many tumor cell lines. In the present study, we investigated the effect of bufalin on the inhibition of an AKT-related signaling pathway, and examined the relationship between regulatory proteins and anti-tumor effects in hepatoma cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 26 publications
1
67
1
Order By: Relevance
“…Our in vivo results revealed that bufalin was able to decrease MMP-2 and MMP-9 expression levels in a dose-dependent manner, whereas our previous in vitro experiments show that bufalin is able to decrease MMP-2 and MMP-9 expressions in hepatoma cell lines [12]. MMP-2 and MMP-9 are zinc-dependent endopeptidases that play critical roles in cancer progression and metastasis [27].…”
Section: Discussionmentioning
confidence: 95%
“…Our in vivo results revealed that bufalin was able to decrease MMP-2 and MMP-9 expression levels in a dose-dependent manner, whereas our previous in vitro experiments show that bufalin is able to decrease MMP-2 and MMP-9 expressions in hepatoma cell lines [12]. MMP-2 and MMP-9 are zinc-dependent endopeptidases that play critical roles in cancer progression and metastasis [27].…”
Section: Discussionmentioning
confidence: 95%
“…In a EGFR mutant lung cancer cell line, it was proved to reverse HGF-induced EGFR-TKIs resistance by blocking the Met/PI3K/Akt signaling pathway (96). In human hepatoma cell lines HCCLM3 and HepG2, bufalin plays a role in suppressing proliferation, migration, invasion and adhesion of hepatoma cells inhibition of the AKT/ GSK3β/β-catenin/E-cadherin signaling pathway (97). There are a number of research reports on the apoptosis effect of bufalin.…”
Section: Steroidmentioning
confidence: 99%
“…Preceding findings have revealed that the anticancer activity of bufalin could be attributed to its prevention of cell proliferation, instruction of apoptosis, disturbance of the cell cycle, and modulation of the immune response 79. Earlier study of ours revealed that bufalin had convincing anticancer growth and reduced the metastatic potentials in the human hepatocellular carcinoma-transplanted tumor model, and the fundamental mechanism was in part mediated by the signaling pathway of the Akt–GSK3β–β-catenin–E-cadherin 10,11. These results indicated that bufalin might be a purposeful constituent for cancer treatment.…”
Section: Introductionmentioning
confidence: 91%